1998
DOI: 10.1002/(sici)1096-9071(199808)55:4<281::aid-jmv5>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of linear antigenic determinants on glycoprotein C of herpes simplex virus type 1 and type 2 recognized by human serum immunoglobulin G antibodies

Abstract: Using membrane-based dekapeptides, the reactivity of human serum antibodies with linear antigenic determinants of herpes simplex virus (HSV) type 1 and type 2 glycoprotein C (gC-1, gC-2) was studied by pep scan and immunodot assay. The entire coding sequences of gC-1 and gC-2 were screened for the presence of linear epitopes by pep scan. Peptides recognized in an HSV-1 type-specific manner were mainly identified within the N-terminal third and at the C-terminus of gC-1, whereas most type-common antibodies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The epitope (210–230 aa) of gC2 was reported to be the immunodominant epitope [23], which is consistent with the prediction in the current study. However, the epitope (216–223 aa) of gC2 was selected in the current study because it had higher antigenicity than the epitope (126–132 aa) of gC2, as shown in the EIA results.…”
Section: Discussionsupporting
confidence: 91%
“…The epitope (210–230 aa) of gC2 was reported to be the immunodominant epitope [23], which is consistent with the prediction in the current study. However, the epitope (216–223 aa) of gC2 was selected in the current study because it had higher antigenicity than the epitope (126–132 aa) of gC2, as shown in the EIA results.…”
Section: Discussionsupporting
confidence: 91%
“…The situation is different for the gC2 peptides: Peptides 11, 12, and 13 reacted with 15 of 16 HSV-2­(+) sera and have very little homology with the corresponding type 1 protein. Both peptides 11 ( 41 ASN­AAP­SAS­PRN­ASA­PRT­TP 60 ), which covers the previously reported epitope gC2 43–52 , and 13 ( 60 TPP­QPR­KAT­KSK­AST­AKP­AP 79 ) also showed some weak reactivity toward a few HSV-1­(+) (Figure ) and negative sera (data not shown), whereas peptide 12 ( 50 RNA­SAP­RTT­PTP­PQP­RKA­TK 69 ) was the most type-specific one and therefore selected for further analysis.…”
Section: Results and Discussionmentioning
confidence: 79%
“…The reason for the retained type-specificity in regions with high similarity might depend on the existence of type-specific amino acids with key functions in antibody binding. As an example, some linear peptides derived from homologous parts of gC were recently shown to be presented in a type-specific manner (Ackermann et al , 1998 ). The importance of key residues has previously been shown in the work of Dolter et al (1992) for mouse MAb reactivity to HSV gC-1.…”
Section: Discussionmentioning
confidence: 99%